CXCR3 identifies human naive CD8+ T cells with enhanced effector differentiation potential - De Simone, Gabriele; Mazza, Emilia M. C.; Cassotta, Antonino; Davydov, Alexey N.; Kuka, Mirela; Zanon, Veronica; De Paoli, Federica; Scamardella, Eloise; Metsger, Maria; Roberto, Alessandra; Pilipow, Karolina; Colombo, Federico S.; et al. (Journal of Immunology, 2019)
In mice, the ability of naive T (TN) cells to mount an effector response correlates with TCR sensitivity for self-derived Ags, which can be quantified indirectly by measuring surface expression levels of CD5. Equivalent findings have not been reported previously in humans. We identified two discrete subsets of human CD8+ TN cells, defined by the absence or presence of the chemokine receptor CXCR3. The more abundant CXCR3+ TN cell subset displayed an effector-like transcriptional profile and expressed TCRs with physicochemical characteristics indicative of enhanced interactions with peptide-HLA class I Ags.Moreover, CXCR3+ TN cells frequently produced IL-2 and TNF in response to nonspecific activation directly ex vivo and differentiated readily into Ag-specific effector cells in vitro. Comparative analyses further revealed that human CXCR3+ TN cells were transcriptionally equivalent to murine CXCR3+ TN cells, which expressed high levels of CD5. These findings provide support for the notion that effector differentiation is shaped by heterogeneity in the preimmune repertoire of human CD8+ T cells.
CRIS-Team Scopus Importer:2023-03-23